Complex Modeling of the Effects of Blasting on the Stability of Surrounding Rocks and Embankment in Water-Conveyance Tunnels - Xian-qi Zhou; Jin Yu; Jin-bi Ye; Shi-yu Liu; Ren-guo Liao; Xiu-wen Li (Complexity)
Blasting in water-conveyance tunnels that cross rivers is vital for the safety and stability of embankments. In this work, a tunnel project that crosses the Yellow River in the north district of the first-phase Eastern Line of the South-to-North Water Diversion Project was selected as the research object. A complex modeling and numerical simulation on embankment stability with regard to the blasting power of the tunnel was conducted using the professional finite difference software FLAC3D to disclose the relationships between the blasting seismic waves with vibration velocity and embankment displacement under different excavation steps. Calculation results demonstrated that displacement generally attenuated from the tunnel wall to the internal structure of rocks under the effect of blasting seismic waves. The tunnel wall was in tension, and tensile stress gradually transformed into compressive stress with increased depth into the rocks. The curtain-grouting zone was mainly concentrated in the compressive zones. For different excavation steps, the vibration velocity at different feature points was high at the beginning of blasting and then gradually decreased. The resultant displacement was relatively small in the early excavation period and slowly increased as blasting progressed. The effects of different excavation steps on the safety of surrounding rocks and embankment under blasting seismic waves were simulated. We found that the blasting-induced vibration velocity was within the safe range of the code and that the calculated displacement was within the allowed range. Numerical simulation was feasible to assess the safety and stability of engineering projects.